2015
DOI: 10.1007/s11356-015-4509-4
|View full text |Cite
|
Sign up to set email alerts
|

Nonylphenol biodegradation, functional gene abundance and bacterial community in bioaugmented sediment: effect of external carbon source

Abstract: Nonylphenol (NP) biodegradation in river sediment using Stenotrophomonas strain Y1 and Sphingobium strain Y2 were proved to be an effective strategy to remediate NP pollution in our earlier study. The purpose of this study is to investigate the influence of glucose addition on their ability to degrade NP in both liquid cultures and sediment microcosms. The shift in bacterial community structure and relative abundance of NP degraders in sediment microcosms were characterized using terminal restriction fragment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…In this sense, MAR is an efficient remediation system. In addition, many sequenced phylotypes, such as Nitrospira sp, Stenotrophomonas sp and Methylobac-5 terium sp have been associated with degradation capabilities (Cycoń et al, 2017;Daims et al, 2001;Wang et al, 2015). In short, the MAR microbial ecosystem studied in this work presents many more phylotypes than previous studies reported in groundwater systems (Logue et al, 2015), and thus, MAR can be considered an efficient remediation system.…”
Section: Matching Groundwater Model Ecological Disturbance Principlementioning
confidence: 72%
“…In this sense, MAR is an efficient remediation system. In addition, many sequenced phylotypes, such as Nitrospira sp, Stenotrophomonas sp and Methylobac-5 terium sp have been associated with degradation capabilities (Cycoń et al, 2017;Daims et al, 2001;Wang et al, 2015). In short, the MAR microbial ecosystem studied in this work presents many more phylotypes than previous studies reported in groundwater systems (Logue et al, 2015), and thus, MAR can be considered an efficient remediation system.…”
Section: Matching Groundwater Model Ecological Disturbance Principlementioning
confidence: 72%
“…Indeed, MAR implies groundwater quality modifications when compared to natural flow conditions. This includes several parameters such as organic matter, dissolved oxygen content, temperature, pH, electrical conductivity and nutrients (Rivett et al, 2008;Zhang et al, 2016). Such disturbances have ecological implications, as all these parameters affect the growth and activity of microorganisms and the corresponding degradation of emerging contaminants (Barbieri et al, 2012;Regnery et al, 2017;Valhondo et al, 2018).…”
Section: Barba Et Al: Microbial Communities In Marmentioning
confidence: 99%
“…Microbial studies linked to MAR practices involve mostly laboratory experiments (Alidina et al, 2014b;Freixa et al, 2015;Li et al, 2013;Rubol et al, 2014). As for microbial MAR field studies, most relevant research is limited to well-injection systems (Ginige et al, 2013;Reed et al, 2008;Zhang et al, 2016) or riverbank filtration conditions (Huang et al, 2015). Onesios-Barry et al (2014) compared results from a column experiment and soil samples in a MAR site in the US, focusing on the microbial populations linked to pharmaceutical and personal care products removal, and concluded that microbial composition and structure of both systems were comparable.…”
Section: Barba Et Al: Microbial Communities In Marmentioning
confidence: 99%
“…The growth of the exogenous degraders is crucial for the efficiency of bioaugmentation efforts (Wang et al 2015a). The growth intensity of NPF-4 in the presence of 4-n-NP (20 mg L −1 ) was tested using dry weight biomass (Sylwia et al 2010) (Fig.…”
Section: The Growth Of Npf-4 In the Presence Of 4-n-npmentioning
confidence: 99%
“…Meanwhile, glucose was the familiar carbon source could alter the microbe community structure lead to promote or inhibit the NP biodegradation efficiency (Mariusz et al 2014;Wang et al 2015a). In the PD media, the strain NPF-4 showed different growth appearance with or without glucose as the co-substrate (Fig.…”
Section: Carbon Source In the Mediamentioning
confidence: 99%